Quantitative analysis of fluorescence recovery after photobleaching and fluorescence loss in photobleaching, with a focus on the dynamics of yes-associated protein - Williamson, Daniel (2021)
Yes-associated protein (YAP) is a transcription regulator with a highly significant role in a wide variety of cancers. When YAP is transported into the cell nucleus, it activates a programme of genes which promote cell proliferation and confer resistance to regulatory signals that normally limit tissue growth. YAP has been shown to promote malignancy and metastasis in tumours and is thus the object of much current biological and medical research. The aim of this thesis is to investigate quantitatively the factors which cause excessive nuclear accumulation of YAP in cancer-associated fibroblasts. To this end, we utilise data from two common experimental techniques, fluorescence recovery after photobleaching (FRAP) and fluorescence loss in photobleaching (FLIP).